SURVEY PENGETAHUAN MASYARAKAT PEDAGANG TENTANG COVID-19 DI KOTA SEMARANG - fitriani kahar; Surati Surati; Djoko Priyatno; Devi Etivia Purlinda; Lilik Setyowatiningsih (Politeknik Kesehatan Kemenkes Makassar, 2021)
The COVID-19 pandemic is a contagious disease that must be watched out for because it causes high mortality rates in several countries around the world. Public knowledge, especially traders, about COVID-19 is important as an effort to prevent the spread of COVID-19, which is increasingly widespread so that people are able to adopt a clean and healthy lifestyle in their daily life. The aim of the research is to conduct a survey of public knowledge about COVID-19 with three indicators, namely knowledge of the disease COVID-19, knowledge of prevention of COVID-19, and knowledge of how to spread COVID-19 so that they can obtain an overview of public knowledge related to COVID-19. This type of research is a qualitative descriptive study with cross sectional design in the community of traders in the Ganesha housing market, Semarang City. The number of samples was 33 people who were determined by total sampling technique. In this study, a questionnaire was used as a data collection tool, with data analyzed descriptively (univariate analysis) presented in the form of a frequency table. The results showed that in general the respondents' knowledge about COVID-19 was in the good category, namely 82%. The results of the knowledge survey from the three indicators were 82% knowledge of the COVID-19 disease followed by the category of how to prevent COVI-19 by 79% and the mode of transmission of COVID-19 which was 70%. It is hoped that there is still a need for continuous education to the community so that people's knowledge can be actualized in the attitudes and behavior of the local community, and as an effort to prevent COVID-19, the application of clean and healthy living habits (PHBS) in the community must be done by getting used to using hands with soap. or hand sanitizer after each activity, and implementing health protocols.